Cesarean - hysterectomy - Alcántara Ascon, René (2015)
This study expresses the experience of Bethlehem Hospital of Trujillo with cesarean hysterectomy (CH) from January 1970 to June 1991. All 63 were emergency cases and corresponded to 0.09% of all births. There was a predominance of patients over 30 years old, multiparous, and pregnancy to term. The indications for operation were uterine rupture (41.2%), placenta accreta (19%), uterine inertia (14.3%), septicemia (12.7%), broad ligament hematoma (4.8%), uterine fibroids (4.8%), and severe chorioamnionitis (3.2%). The type of hysterectomy, type of anesthesia, operative time, and hospital stay were discussed. The complications that arose were multiple, the most frequent hypovolemic shock, severe anemia, and infection of the surgical wound. 3 patients died from hypovolemic shock and septic shock 2.